2021
DOI: 10.3390/app11188294
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Work Gloves in Terms of the Strengths of Hand Grip, One-Handed Carrying, and Leg Lifting

Abstract: Gloves are used at workplaces to protect hands and fingers from potential hazards. Three types of work gloves were assessed in terms of the strength of grip, carrying, and lifting. Thirty adults (14 males and 16 females) joined as human participants. The strength data were measured under bare hand and three gloved conditions. The grip spans in the grip strength measurements included 45 mm, 55 mm, 65 mm, and 75 mm. The carrying strength was measured for both dominant and non-dominant hands under leg straight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Gloves can negatively affect grip strength. Most previous studies demonstrated that wearing any type of gloves has a negative effect on grip strength, for example Wimer et al [ 18 ], Ramadan [ 19 ], and Zhao et al [ 20 ]. However, the reducing effect of wearing gloves on grip strength is not supported by all studies.…”
Section: Introductionmentioning
confidence: 99%
“…Gloves can negatively affect grip strength. Most previous studies demonstrated that wearing any type of gloves has a negative effect on grip strength, for example Wimer et al [ 18 ], Ramadan [ 19 ], and Zhao et al [ 20 ]. However, the reducing effect of wearing gloves on grip strength is not supported by all studies.…”
Section: Introductionmentioning
confidence: 99%